Dynamic molecular changes during the first week of human life follow a robust developmental trajectory - Amy H. Lee (Nature Portfolio, 2019)
The first week of life impacts health for all of life, but the mechanisms are little-understood. Here the authors extract multi-omic data from small volumes of blood to study the dynamic molecular changes during the first week of life, revealing a robust developmental trajectory common to different populations.